Upaya Mengembangkan Kreativitas Anak melalui Permainan Warna dengan Media Benang di RA At Taslim Pangalengan - Sinta Silvia (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This study aims to develop children's creativity through playing with colors using yarn in the B RA group at Taslim PangalenganRegency. Color game activities with thread media can attract children's interest in developing their creativity. The subjects in this study were the children of group B RA At Taslim Pangalengan, Bandung Regency, with a total of 10 children. Thevariable associated with this research is creativity. The method used to collect data about children's creativity uses observation, performance, and interview methods. This research was conducted into two cycles. This type of research is Classroom Action Research (CAR). Researchers have made improvements in the learning process carried out for 2 days in the cycle and continued with 2 days in cycle 2, considering that the child's creativity has reached the target level of completeness. Based on data analysis through playing with colors with thread media, it can develop children's creativity in the B RA group at Taslim Pangalengan, Bandung Regency